2020
DOI: 10.1177/0963662519897574
|View full text |Cite
|
Sign up to set email alerts
|

‘It is not entirely healthy.’ A qualitative study into public appraisals of uncertain risks of chemical substances in food

Abstract: For some chemical substances in food, scientific uncertainty prevents definitive statements about the presence of risk for human health. In this qualitative study, we explored the public’s understanding and risk appraisal of these substances. During semi-structured interviews, participants from the public were presented with inconclusive risk information about either a food additive or one of two food contaminants. Findings show that interviewees had no prior knowledge and constructed their risk appraisal on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…Citizens and consumers often refer to hormones, antibiotics, pesticides, transgenic components, and feed additives collectively as “chemicals” and link them with lack of naturalness in production systems, and with lower animal welfare and product quality [ 35 , 51 , 52 ]. As shown in this study, Jansen et al [ 53 ] found that some people have negative attitudes towards chemicals in food and consider them unnatural and detrimental to health, and associate “chemical” with danger. Concern that immunocastration (and to a lesser extent, pain medications) would leave residues in the meat was also reported by participants, as shown by others [ 47 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Citizens and consumers often refer to hormones, antibiotics, pesticides, transgenic components, and feed additives collectively as “chemicals” and link them with lack of naturalness in production systems, and with lower animal welfare and product quality [ 35 , 51 , 52 ]. As shown in this study, Jansen et al [ 53 ] found that some people have negative attitudes towards chemicals in food and consider them unnatural and detrimental to health, and associate “chemical” with danger. Concern that immunocastration (and to a lesser extent, pain medications) would leave residues in the meat was also reported by participants, as shown by others [ 47 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 56%
“…For example, the name of a technology influences public attitudes [ 64 ], so the term immunocastration may have induced some people to think of controversies like vaccines or biotechnologies, adding to distrust. Additionally, it has been shown that interpreting risk messages is not straightforward, and lay understanding may not be in line with the intended scientific meaning [ 53 ]. Lastly, part of the participants said that they did not trust most of the sources of information on animal production, which may be why some participants implied having low confidence in the information presented.…”
Section: Discussionmentioning
confidence: 99%
“…Also, stimulating careful evaluation of the information about risks can serve to amplify signals or aspects previously ignored or overlooked and affect how this information is perceived and reacted to. It may, for example, lead to cynicism or rejection of information, decrease the perception of safety of food products ( Frewer et al, 2003 , Jansen et al, 2019 ) and negatively affect levels of trust. This may spur responses resembling those seen in 2014–2016.…”
Section: An Uncertainty-based Risk Understanding Promotes Higher Levementioning
confidence: 99%
“…La segunda categoría se refiere al procesamiento de alimentos después de ser cosechados, y distingue entre los ingredientes utilizados y el proceso de producción en sí mismo. En cuanto a los ingredientes, los consumidores parecen dar importancia a la ausencia de ciertos componentes considerados negativos (principalmente aditivos, pero también conservantes, colorantes artificiales y sabores, hormonas, pesticidas y organismos genéticamente modificados) más que a la presencia de ciertos componentes positivos (ingredientes naturales) (España 2008;Jansen et al, 2020). Los productos deben ser tan mínimamente procesados como sea posible, incluso con parecido a los alimentos caseros.…”
Section: Alimento Natural/no Naturalunclassified
“…a) Centrarse en la composición química de los alimentos más que en los procesos por los cuales se obtienen, que suelen ser más relevantes para los estudiantes y ciudadanos (Rozín et al 2004, Jansen et al 2020. Los estudiantes tienen que apreciar y reconocer que la composición química es lo realmente relevante y lo que puede o no, tener efecto sobre la salud.…”
Section: Implicaciones Educativasunclassified